2007
DOI: 10.1164/rccm.200604-511oc
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Attenuates Sepsis-induced Acute Lung Injury and Mortality in Rats

Abstract: Rationale: Our study has shown that plasma levels of ghrelin, a stomach-derived peptide, are significantly reduced in sepsis, and that ghrelin administration improves organ blood flow via a nuclear factor (NF)-kB-dependent pathway. However, it remains unknown whether ghrelin has any protective effects on severe sepsis-induced acute lung injury (ALI) and, if so, whether inhibition of NF-kB plays any role in it. Objectives: To test the hypothesis that ghrelin reduces severe sepsisinduced ALI and mortality throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 53 publications
4
157
1
5
Order By: Relevance
“…In healthy human subjects, LPS administration induced a biphasic change in circulating ghrelin levels, with a rapid increase reaching the maximum after the pick of TNF-a and a subsequent decrease with the nadir 5 h after LPS administration (Vila et al 2007). In rodent models of sepsis, induced either by LPS injection or caecal ligation and perforation, ghrelin treatment reduced the level of pro-inflammatory cytokines both in circulation and in tissues impacted by sepsis, such as lung and kidney (Peng et al 2012;Wang et al 2009;Wu et al 2007b). It has been shown that ghrelin protective effects are mediated by the activation of the vagal nerve (Wu et al 2007a), inhibition of sympathetic nervous system, seen as reduced gut-derived norepinephrine release (Jacob et al 2010;Wu et al 2007c), and inhibition of NF-jB pathway (Peng et al 2012;Wu et al 2007b).…”
Section: Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy human subjects, LPS administration induced a biphasic change in circulating ghrelin levels, with a rapid increase reaching the maximum after the pick of TNF-a and a subsequent decrease with the nadir 5 h after LPS administration (Vila et al 2007). In rodent models of sepsis, induced either by LPS injection or caecal ligation and perforation, ghrelin treatment reduced the level of pro-inflammatory cytokines both in circulation and in tissues impacted by sepsis, such as lung and kidney (Peng et al 2012;Wang et al 2009;Wu et al 2007b). It has been shown that ghrelin protective effects are mediated by the activation of the vagal nerve (Wu et al 2007a), inhibition of sympathetic nervous system, seen as reduced gut-derived norepinephrine release (Jacob et al 2010;Wu et al 2007c), and inhibition of NF-jB pathway (Peng et al 2012;Wu et al 2007b).…”
Section: Cachexiamentioning
confidence: 99%
“…In rodent models of sepsis, induced either by LPS injection or caecal ligation and perforation, ghrelin treatment reduced the level of pro-inflammatory cytokines both in circulation and in tissues impacted by sepsis, such as lung and kidney (Peng et al 2012;Wang et al 2009;Wu et al 2007b). It has been shown that ghrelin protective effects are mediated by the activation of the vagal nerve (Wu et al 2007a), inhibition of sympathetic nervous system, seen as reduced gut-derived norepinephrine release (Jacob et al 2010;Wu et al 2007c), and inhibition of NF-jB pathway (Peng et al 2012;Wu et al 2007b). In addition, ghrelin exerts its protective action through inhibition of high-mobility group box release (Chorny et al 2008;Wu et al 2009) and through an antimicrobial activity (Chorny et al 2008).…”
Section: Cachexiamentioning
confidence: 99%
“…Ghrelin has several physiological functions in addition to the secretion of GH, including the promotion of the appetite signal that antagonizes leptin in the hypothalamus [17], stimulation of gastrointestinal activity (e.g., peristalsis, gastric acid secretion, and pancreatic excretion through the vagal nerves) [18], and regulation of fat metabolism [19] (Table 1). Ghrelin also mitigates proinflammatory cytokine production and attenuates the stress signal [20]. Ghrelin exists as two major molecular forms: acyl ghrelin and des-acyl ghrelin.…”
Section: The Discovery Of Ghrelin and Its Featuresmentioning
confidence: 99%
“…GH regulates IGF-I levels, promotes anabolism, and increases muscle strength. Ghrelin enhances lipolysis via GH and stimulates protein synthesis, myoblast differentiation, and muscle growth via IGF-1 Antiinflammatory action [20,63,64] Ghrelin inhibits the activation of NF-jB, a transcription factor known to control the production of multiple proinflammatory cytokines during inflammatory insults Stimulation of gastrointestinal peristalsis [18] Ghrelin acts on motor neurons in the myenteric plexus, activates a vago-vagal reflex, or may stimulate central pathways Augmentation of cardiac output and reduction of blood pressure [26] Ghrelin improves myocardial structure and function in chronic heart failure (CHF) via its GH-releasing effects Inhibition of insulin secretion [65,66] Ghrelin has obesogenic/diabetogenic properties. These properties may be direct effects of ghrelin on pancreatic islet function and/or indirect effects through the modulation of GH secretion Application of ghrelin administration 201…”
Section: Gastrectomy and Ghrelin Secretionmentioning
confidence: 99%
“…It has been linked to the regulation of pituitary hormone secretion, feeding, energy homeostasis, gastrointestinal function, cardiovascular system, and immune system (16)(17)(18). Our recent studies have shown that circulating levels of ghrelin decreased significantly in a rat model of polymicrobial sepsis induced by cecal ligation and puncture (CLP), and ghrelin administration decreases inflammatory responses, improves organ blood flow, attenuates tissue injury, and reduces mortality under such conditions (18)(19)(20)(21). However, it remains unknown whether ghrelin ameliorates sepsis-induced organ injury and mortality after radiation exposure.…”
Section: Introductionmentioning
confidence: 99%